Correction: A Stochastic Model of the Yeast Cell Cycle Reveals Roles for Feedback Regulation in Limiting Cellular Variability. - PLOS Computational Biology Staff (PLoS Computational Biology, 2017)
[This corrects the article DOI: 10.1371/journal.pcbi.1005230.].